Ketika Pengalaman Bertemu Inovasi: Eksplorasi Perbedaan dan Kekuatan Gaya Mengajar Guru Senior dan Guru Muda di Era Pembelajaran Modern - Maisyaroh; Ratna Puspita Sari; Selly Perisca Putri; Muhammad Fendrik; Cici Oktaviani (Publikasi Inspirasi Indonesia, 2026)
This study was motivated by the differences in teaching styles between senior teachers and young teachers in responding to the demands of modern learning in elementary schools. The rapid development of technology and changes in educational paradigms require teachers to implement effective, innovative, and student-centered learning practices. This study aimed to analyze the differences and strengths of the teaching styles of senior and young teachers in creating effective learning environments at SD Negeri 013 Kepenuhan. A qualitative descriptive approach was employed, with data collected through observations, interviews, and documentation. The participants consisted of senior and young teachers who actively participated in the teaching and learning process. The findings revealed that senior teachers tend to emphasize classroom management, learning discipline, and the use of teaching experiences accumulated over many years. Meanwhile, young teachers are more likely to utilize digital technology, interactive learning media, and innovative teaching methods that encourage student engagement. Despite these differences, both groups demonstrated complementary strengths in supporting effective learning. Senior teachers contributed stability, pedagogical wisdom, and classroom experience, whereas young teachers brought creativity, technological adaptability, and innovation. Therefore, collaboration between senior and young teachers is essential to create a balanced learning environment that integrates experience and innovation to improve the quality of education in the modern era.